1989
DOI: 10.1128/jb.171.12.6791-6799.1989
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of 1,2-dichloroethane degradation genes of Xanthobacter autotrophicus GJ10 and expression and sequencing of the dhlA gene

Abstract: A gene bank from the chlorinated hydrocarbon-degrading bacterium Xanthobacter autotrophicus GJ10 was prepared in the broad-host-range cosmid vector pLAFR1. By using mutants impaired in dichloroethane utilization and strains lacking dehalogenase activities, several genes involved in 1,2-dichloroethane metabolism were isolated. The haloalkane dehalogenase gene dhLA was subcloned, and it was efficiently expressed from its own constitutive promoter in strains of a Pseudomonas sp., Escherichia coli, and a Xanthobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
156
1
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(162 citation statements)
references
References 34 publications
4
156
1
1
Order By: Relevance
“…Moraxella B (DehH1, Genbank/EMBL Accession Number D90422; Kawasaki et al, 1992), tetrachlorocyclohexadiene dehalogenase from Sphingomonas paucimobilis (LinB, D14594; Nagata et al, 1993), and 1-chloroalkane halidohydrolase from Rhodococcus rhodochrous NCIMB13064 (DhaA, L49435; Kulakova et al, 1997) showed that they have considerable homology with DhlA (M26950), suggesting FIGURE 2: Sequence alignment of haloalkane dehalogenase from Xanthobacter autotrophicus GJ10 (DhlA; Janssen et al, 1989), haloacid dehalogenase from Moraxella B (DehH1; Kawasaki et al, 1992), tetrachlorocyclohexadiene dehalogenase from Sphingomonas paucimobilis (LinB; Nagata et al, 1993), and 1-chloroalkane halidohydrolase from Rhodococcus rhodochrous NCIMB13064 (DhaA; Kulakova et al, 1997). The sequence comparison was carried out using the program DNASTAR (DNASTAR Inc., Madison, WI).…”
Section: Sequence Alignment Of R/ -Hydrolase Fold Dehalogenases Sequmentioning
confidence: 99%
“…Moraxella B (DehH1, Genbank/EMBL Accession Number D90422; Kawasaki et al, 1992), tetrachlorocyclohexadiene dehalogenase from Sphingomonas paucimobilis (LinB, D14594; Nagata et al, 1993), and 1-chloroalkane halidohydrolase from Rhodococcus rhodochrous NCIMB13064 (DhaA, L49435; Kulakova et al, 1997) showed that they have considerable homology with DhlA (M26950), suggesting FIGURE 2: Sequence alignment of haloalkane dehalogenase from Xanthobacter autotrophicus GJ10 (DhlA; Janssen et al, 1989), haloacid dehalogenase from Moraxella B (DehH1; Kawasaki et al, 1992), tetrachlorocyclohexadiene dehalogenase from Sphingomonas paucimobilis (LinB; Nagata et al, 1993), and 1-chloroalkane halidohydrolase from Rhodococcus rhodochrous NCIMB13064 (DhaA; Kulakova et al, 1997). The sequence comparison was carried out using the program DNASTAR (DNASTAR Inc., Madison, WI).…”
Section: Sequence Alignment Of R/ -Hydrolase Fold Dehalogenases Sequmentioning
confidence: 99%
“…2). Among these, the haloalkane dehalogenase has been studied in most detail (Janssen et al, 1989;Verschueren et al, 1993). On the basis of its three-dimensional structure it has been grouped into the superfamily of a//l-hydrolase-fold enzymes, the most prominent member of which is acetylcholine esterase (Franken et al, 1991 ;Ollis et al, 1992).…”
Section: Halomentioning
confidence: 99%
“…However, IS1358 from V. cholerae (15) exhibited a 54% nucleotide residue identity with PGIS2. Protein sequence database searches also revealed significant homology between the putative polypeptide encoded by PGIS2 and the putative transposase of IS1358 from V. cholerae (15), the protein encoded by A. salmonicida IS element ISAS1 (5), the predicted product of H-rpt from E. coli K-12 (16), and a hypothetical protein encoded by a long ORF downstream of the dhlA gene of X. autotrophicus GJ10 (9). The amino acid alignment indicated that these proteins are more conserved in the central region (Fig.…”
mentioning
confidence: 99%
“…In this study we identified a second endogenous IS element in P. gingivalis. The predicted protein encoded by PGIS2 exhibits a high degree of homology to the putative transposases of IS1358 and ISAS1 from V. cholerae and A. salmonicida, respectively, the predicted product of H-rpt from E. coli K-12 (16), and a hypothetical protein encoded by a long ORF downstream of the dhlA gene of X. autotrophicus GJ10 (9). The additional copy of PGIS2 in P. gingivalis Tn4351 transconjugant MSM-1 suggests that either transposition of the endogenous PGIS2 element occurred following transposition of Tn4351 or transposition of PGIS2 spontaneously occurred during laboratory passage.…”
mentioning
confidence: 99%
See 1 more Smart Citation